The ways that never parted. Jews and Christians in late antiquity and the early Middle Ages. Edited by Adam H. Becker and Annette Yoshiko Reed. (Texts and Studies in Ancient Judaism, 95.) Pp. viii+413. Tübingen: J. C. B. Mohr (Paul Siebeck), 2003. €74. 3 16 147966 1; 0721 8753 - Paget, James Carleton (The journal of ecclesiastical history, 2004)
The ways that never parted. Jews and Christians in late antiquity and the early Middle Ages. Edited by Adam H. Becker and Annette Yoshiko Reed. (Texts and Studies in Ancient Judaism, 95.) Pp. viii+413. Tübingen: J. C. B. Mohr (Paul Siebeck), 2003. €74. 3 16 147966 1; 0721 8753 - Volume 55 Issue 3